Coordination training system for annual training cycle of elite blind biathletes - Zebzeev, V. V.; Ivanov, D. I.; Melnikova, L. V.; Zdanovich, O. S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to test and analyze benefits of a coordination training system for elite blind biathletes in an annual training cycle. Methods and structure of the study. The coordination training system was tested at Snezhinka Winter Sports Federal Training Center in September 2020 to June 2021. We sampled for the study the elite blind biathletes (n=7, including 3, 2 and 2 Class B1, B2 and B3 biathletes, respectively). The blind biathlon sample training was complemented by the coordination training system in 2-week field trainings and other training and competitive periods within an annual training cycle. Progress of the blind biathlon sample in the annual training cycle was tested in the following three periods: preparatory period; beginner coordination training (CT1) and final coordination training (CT2) ones. The coordination skills were tested by a computerized Stabilan 01-02 stabilometry test system that generates test data with a sampling frequency of 50 Hz per second. The test set included Qualification, Target Shooting and Stability tests that produced the following tests data: BMC (body mass center) total (mm); confidence ellipse size (mm2); equilibrium function quality (%); movement redirecting sharpness ratio (%); front/ back/ left/ right deviation (mm); and the total movement zone (mm2). The sample was tested in a relatively quiescent state, with the test data processed by a standard mathematical statistics toolkit. We used a nonparametric Wilcoxon test for related samples - since the sample was very limited. Results and conclusion. The new coordination training system for elite blind biathletes in an annual training cycle was tested beneficial due to the practices centered on the integrated coordination skills in the preparatory period; followed by the skiing balance and coordination skills improvement practices in the beginner coordination training period (with the shooting skills given a lower priority in this period); and a special focus on the shooting accuracy improvement practices in the final coordination training period (with the skiing coordination skills given a lower priority in this period).